2008
DOI: 10.1128/ec.00148-08
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Signals Regulate Targeting of Glycosylphosphatidylinositol-Anchored Proteins to the Cell Wall or Plasma Membrane in Candida albicans

Abstract: Fungal glycosylphosphatidylinositol (GPI)-anchored proteins localize to the plasma membrane (PM), cell wall (CW), or both. To study signals that regulate PM versus CW targeting in Candida albicans, we (i) fused the N and/or C termini of the GPI CW protein Hwp1p and the GPI PM protein Ecm331p to green fluorescent protein (GFP) and (ii) expressed and localized the resulting fusions. Forty-seven amino acids from the C terminus of Hwp1p were sufficient to target GFP to the CW, and 66 amino acids from the C terminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…1B, C). The amino acids upstream of the v sites were also conserved, and the absence of a dibasic motif and occurrence of an acidic residue suggested a cell wall location for both Pga59 and Pga62 (Caro et al, 1997;Mao et al, 2008). Pga62 differed from Pga59 by the occurrence of an additional 42 aa repeat (Fig.…”
Section: Pga59 and Pga62 Encode Related Putative Gpimodified Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B, C). The amino acids upstream of the v sites were also conserved, and the absence of a dibasic motif and occurrence of an acidic residue suggested a cell wall location for both Pga59 and Pga62 (Caro et al, 1997;Mao et al, 2008). Pga62 differed from Pga59 by the occurrence of an additional 42 aa repeat (Fig.…”
Section: Pga59 and Pga62 Encode Related Putative Gpimodified Proteinsmentioning
confidence: 99%
“…In the case of C. albicans, localization of GPI-modified proteins appears to be dependent on similar as well as additional determinants (Richard & Plaine, 2007). For instance, Mao et al (2008) have shown that the occurrence of an aromatic residue and an acidic residue in positions v-2 and v-1, respectively, promotes cell wall localization of C. albicans GPI-modified proteins. There are 115 putative GPI-modified proteins in C. albicans and most of them have unknown functions.…”
mentioning
confidence: 99%
“…We have name these proteins GPI-anchored cell wall proteins hereafter in the text. Several studies have attempted to identify the signal governing the final localization of GPI-anchored proteins, and they pointed out the crucial role of basic amino acids upstream of the GPI anchor attachment site (the site) for plasma membrane retention (8,24,25,29,47).…”
mentioning
confidence: 99%
“…These experiments identified the omega cleavage site. Further domain exchange and mutagenesis studies identified which residues dictated cell wall or plasma membrane localization (Mao et al, 2008).…”
Section: Other Applicationsmentioning
confidence: 99%
“…Site-directed mutagenesis has been used to determine how GPI-tagged proteins discriminate between localization to the plasma membrane and cell wall (Mao et al, 2008). N and C termini of cell wall or plasma proteins were fused to GFP.…”
Section: Other Applicationsmentioning
confidence: 99%